Consumer Purchase Intention towards Diamond Jewelry in Indonesia - Amelia, Sindy Yurezka; Hudrasyah, Herry (Journal of Business and Management, 2016)
Abstract.This research focused on diamond jewelry industry in Indonesia that keep increasing every year based on Canadean’s extensive market research report. In comparison, according to the latest data from Statistics Indonesia (BPS), Indonesia’s gross domestic product (GDP) growth decrease quite significantly in the last 5 years. This means the related causes have contradiction and have to be analyzed clearly about factors in consumer’s behavior towards diamond jewelry. This research analyzed reasons why consumers purchase and consume diamond jewelry and what are their intention in buying diamond jewelry including their motivations and considerations in buying those luxury goods by using qualitative interviewing techniques. The methodology is in-depth interview with 7 respondents who will be the key informants of this study. Results of the interviews revealed that the majority of the respondents are mostly motivated by their self-identity, need for uniqueness and also need for status when intending to buy diamond jewelry. The respondents also consider diamond jewelry as an investment to be their motivator, since it can be resell and be trade in for the new one. Nevertheless, price was found to be the most frequent barrier when making decisions to purchase or not.Keyword: Consumers behavior, luxury goods, diamond jewelry, purchase intention, personality factors